Anomalous branching order of the superior and lateral thoracic arteries - (:unkn) unknown (WILEY-LISS, 1997)
The superior thoracic and lateral thoracic arteries usually arise from the axillary artery as the first and second branches, respectively. Although anomalies have been described, no reports of a reversal of the order of origin have been found. In two cadaveric dissections, the lateral thoracic artery was found to arise cephalad to the superior thoracic artery. (C) 1997 Wiley-Liss, Inc.
Keywords: superior (supreme, highest) thoracic artery; lateral thoracic artery; axillary artery; variation